Evaluation of new guidelines for ROP screening in Sweden using SWEDROP – a national quality register. (18th July 2014) - Holmström, Gerd; Hellström, Ann; Jakobsson, Peter; Lundgren, Pia; Tornqvist, Kristina; Wallin, Agneta
Abstract Purpose To investigate whether recent Swedish guidelines for Retinopathy of Prematurity (ROP) screening, that is, a gestational age (GA) at birth of <31 weeks (w), are applicable in a new national cohort of prematurely born infants. Methods SWEDROP is a national register for ROP, initiated in 2006. The present paper reports on data from the register on various aspects of screening for ROP in infants born between 2010 and 2011 and compares the results with those for a previously published cohort born between 2008 and 2009. Results During the study period, 1744 infants were screened for ROP. Mean GA was 28.4 w (22–31), and mean birth weight was 1239 g (382–2615). Screening started at postnatal age (PNA) 5.4 w (0.4–13.3) and postmenstrual age (PMA) 33.8 w (24.9–50.1) Mean number of examinations was 5.4 per infant (1–38). Mild (stages 1–2) and severe (≥ stage 3) ROP was found in 15.4% and 8.7%, respectively. Treatment was performed in 4.2% (73/1744) of the infants, but in none with a GA of 30 weeks or more. The first treatment was performed at a mean PNA and PMA of 12.7 w (7.7–25.4) and 37.4 w (32.1–51.4), respectively. Conclusions Recently introduced new guidelines for ROP screening in Sweden remain applicable. Reassuringly, in infants born between 2010 and 2011, incidence of ROP, frequency and timing of treatment, frequency and timing of examinations and national coverage of ROP screening remained almost identical to those for a previous cohort from 2008 to 2009. The two SWEDROP cohorts provide a basis for discussion among Swedish ophthalmologists and neonatologists on the question of further lowering the upper screening limit with 1 week.